Strategi Pembelajaran Gamifikasi untuk Meningkatkan Motivasi Belajar Bahasa Arab Siswa di Sekolah Dasar Islam Terpadu - Putra Fadliardi, Nadhif Athallah; Mardhotillah, Shafa Aurel; Ana Dzukhoiriyah; Maswani (Institut Muslim Cendekia, 2025)
This study aims to describe and analyze the Arabic language learning strategies implemented at an Integrated Islamic Elementary School (SDIT) in Depok, focusing on the use of games to enhance student motivation. The research problem arises from common challenges in teaching Arabic at the elementary level, such as limited language exposure, difficulties in writing, and an unsupportive learning environment. The novelty of this research lies in the use of gamification as the primary strategy for teaching Arabic, which is linked to students’ Islamic identity, thereby encouraging them to connect the lesson content with daily worship and fostering greater interest in the subject. This study employs a qualitative method, with data collected through in-depth interviews with an Arabic teacher and non-participant observations. The findings reveal that the school applies a self-developed curriculum emphasizing word-by-word translation from the Qur’an and Hadith, as well as practical daily conversations. A prominent learning strategy is the use of gamification, such as competitive group games and word-matching activities, to maintain student enthusiasm. Based on interviews, observations, and student responses, the gamification strategies applied were found to be effective in addressing the primary challenge, students’ low motivation in learning Arabic. This approach can serve as a reference for other schools seeking to develop enjoyable Arabic learning methods that enhance student motivation.